2023
DOI: 10.1126/sciadv.abq8225
|View full text |Cite
|
Sign up to set email alerts
|

A bispecific glycopeptide spatiotemporally regulates tumor microenvironment for inhibiting bladder cancer recurrence

Abstract: Up to 75% of bladder cancer patients suffer from recurrence due to postoperative tumor implantation. However, clinically used Bacillus Calmette-Guerin (BCG) treatment failed to inhibit the recurrence. Here, we report a bispecific glycopeptide (bsGP) that simultaneously targets CD206 on tumor-associated macrophages (TAMs) and CXCR4 on tumor cells. bsGP repolarizes protumoral M2-like TAMs to antitumor M1-like that mediated cytotoxicity and T cell recruitment. Meanwhile, bsGP is cleaved by the MMP-2 enzyme to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This designed and synthesized NLS-FF-T (HCA-K(T)LVFF-PEG-VKRKKKP) peptide was comprised of five discrete functional motifs: (i) coumarin (HCA), as a hydrophobic core to induce the formation of nanoparticles; (ii) thymine, as ATP selective sequestering moiety [ 18 ]; (iii) KLVFF, β-sheet-forming peptide domain derived from β-amyloid (Aβ) peptide [ 27–29 ]; (iv) PEG, as a hydrophilic surface to induce the formation of nanoparticles and (v) the VKRKKKP peptide Karyopherin Subunit Alpha-2 (KPNA2)-binding domain, derived from the primary sequence of NLS ( Figs S1 and S2 ) [ 30 , 31 ]. NLS-FF (HCA-KLVFF-PEG-VKRKKKP), FF-T (HCA-K(T)LVFF-PEG2) and NLS-T (HCA-K(T)LV-PEG-VKRKKKP) were designed and synthesized as controls ( Figs S3–S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…This designed and synthesized NLS-FF-T (HCA-K(T)LVFF-PEG-VKRKKKP) peptide was comprised of five discrete functional motifs: (i) coumarin (HCA), as a hydrophobic core to induce the formation of nanoparticles; (ii) thymine, as ATP selective sequestering moiety [ 18 ]; (iii) KLVFF, β-sheet-forming peptide domain derived from β-amyloid (Aβ) peptide [ 27–29 ]; (iv) PEG, as a hydrophilic surface to induce the formation of nanoparticles and (v) the VKRKKKP peptide Karyopherin Subunit Alpha-2 (KPNA2)-binding domain, derived from the primary sequence of NLS ( Figs S1 and S2 ) [ 30 , 31 ]. NLS-FF (HCA-KLVFF-PEG-VKRKKKP), FF-T (HCA-K(T)LVFF-PEG2) and NLS-T (HCA-K(T)LV-PEG-VKRKKKP) were designed and synthesized as controls ( Figs S3–S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…(c) Binding affinity between CXCR4 and nano-GP by MST. Reproduced from ref . Available under a Creative Commons Attribution Non-Commercial License 4.0 (CC BY-NC).…”
Section: Current Strategies Targeting Tamsmentioning
confidence: 99%
“…Owing to the advantages of deep tumor penetration and enhanced hypoxic TAMs repolarization, this glycopeptide with anti-PD-1 antibody achieved a 90.2% tumor inhibitory rate in the TAMsabundant 4T1-breast cancer model. Furthermore, to further improve the spatiotemporal specificity for immunotherapy, An et al reported a bispecific glycopeptide that targeted CD206 on M2-like TAMs and CXCR4 receptors on tumor cells for inhibiting bladder cancer recurrence (Figure 7c) [400]. The peptide consisted of 4 modules, including (i) a CD206targeting motif with (ii) an MMP-2 cleavable linker, (iii) a CXCR4-targeting motif, and (iv) a self-assembly motif (peptide sequence: LGASWHRPDKK(PLGYLG-(man) 3 )LVFFAECG).…”
Section: Immune-reprogramming Nanomaterialsmentioning
confidence: 99%